Targeting Macrophages as a Therapeutic Option in Coronavirus Disease 2019 - Gracia-Hernandez, Maria; Sotomayor, Eduardo M.; Villagra, Alejandro (Frontiers in Pharmacology, 2020)
Immune cells of the monocyte/macrophage lineage are characterized by their diversity, plasticity, and variety of functions. Among them, macrophages play a central role in antiviral responses, tissue repair, and fibrosis. Macrophages can be reprogrammed by environmental cues, thus changing their phenotype during an antiviral immune response as the viral infection progresses. While M1-like macrophages are essential for initial antiviral immune responses, M2-like macrophages are critical for tissue repair after pathogen clearance. Numerous reports have evaluated the detrimental effects that coronaviruses, e.g., HCoV-229E, SARS-CoV, MERS-CoV, and SARS-CoV-2, have on the antiviral immune response and macrophage functions. In this review, we have addressed the breadth of macrophage phenotypes during the antiviral response and provided an overview of the role of macrophages in coronavirus infections. We also discussed therapeutic approaches for targeting macrophage-induced complications, currently under evaluation in clinical trials for COVID-19 patients. Additionally, we have proposed alternative approaches that target macrophage recruitment, interferon signaling, cytokine storm, pulmonary fibrosis, and hypercoagulability.